Effect of indigenous arbuscular - mycorrhiza (Glomus spp) on apple (Malus domestica) seedlings grown in replant disease soil - MEHTA, PRAVEEN; BHARAT, NARENDER K (The Indian Journal of Agricultural Sciences, 2026)
Poor growth and short life of newly planted apple trees at old apple site is known as apple (Malus domestica Borkh)replant problem. It is very difficult to be managed due to its complex etiology. To find out a sustainable management of this problem, effect of indigenous arbuscular-mycorrhizal fungi (AMF) was observed on growth of apple seedlings grown in apple replant diseased (ARD) soil. Out of five AMF isolates collected from apple orchards in Himachal Pradesh, one isolate AMFS-2 (Glomus fasciculatum) was selected on the basis of its colonization and growth promotion in inoculated apple seedlings. This AMF isolate was then used to see its effect on growth of apple seedlings grown in ARD soil collected from replant affected apple orchards. The AMF inoculation resulted significant increase in growth parameters, viz. plant height, stem diameter, internodal length, leaf area, shoot/ root fresh and dry weight of inoculated seedlings as compared to uninoculated seedlings grown in ARD soil in pot cultures. The effect of AMF inoculation on seedling growth was more when these were grown in ARD or virgin soil fumigated with formaldehyde. The phosphorus content of AMF inoculated seedlings were significantly more than uninoculated ones. The population of fungi, bacteria and actinomycetes was also less in the rhizosphere of mycorrhizal inoculated apple seedlings grown in ARD soil.